Habima in between Studio and Theatre: The Lack of Artistic Leadership - Tartakovsky, Elena (MiKAN, 2006)
This article presents Habima's collective organization between 1928and 1969, and analyses the problematic lack of artistic leadership inthat period. Habima began as a jewish drama studio in Moscow in1917, whose artistic, organizational and ethical foundations wereestablished in the context of the collectivist ideology of the StudioMovement that developed in Russian theatre at the beginning of the20th century. Habima's status as an "exemplary studio" contributedto its extraordinary artistic successes. Later, however, the collectivistideology conflicted with the theatre's professional interests, preventingdelegation of authority to relevant individual professionals. Thisarticle discusses the three ways (leadership by Russian, Germanor resident directors), in which Habima confronted the problem ofartistic leadership, and analyses the reasons for its limited success.